Experimental study in pulmonary artery sealing with a vessel-sealing device. (July 2016) - Yamada, Tetsu; Sowa, Terumasa; Bando, Toru; Date, Hiroshi
Background: The development of vessel-sealing devices will facilitate safety in video-assisted thoracoscopic surgery. Our objective was to evaluate the feasibility and safety of sealing pulmonary arteries with the Enseal tissue-sealing device. Methods: Pulmonary arteries from beagle dogs (mean body weight 13.1 kg, range 10.5–15.4 kg) were divided into 3 groups according to the in-vivo sealing method used (Enseal, ligation, and proximal ligation plus distal Enseal) and extracted to evaluate the pressure tolerance up to 75 mm Hg at the sealed end. A left lower lobectomy was performed to evaluate chronic-phase durability of the sealed stumps in a survival model. Two or three branches of the pulmonary arteries in each dog were allocated to each of the 3 groups. After the scheduled survival period, the pulmonary arteries were sampled. Results: Pressure tolerance at the sealed end was evaluated in 91 pulmonary artery sections. All sealed ends showed pressure tolerance >75 mm Hg. A left lower lobectomy was performed in 13 dogs in which 35 pulmonary artery sections had been allocated into the 3 groups. No sealing failure was found, and pathological findings showed healing and persistent hemostasis at all sealed ends of the pulmonary arteries after 2 and 4 weeks of the survival period. Conclusions: Pulmonary arteries sealed in vivo with the Enseal device showed pressure tolerance >75 mm Hg in the acute phase, and persistent hemostasis after 2 or 4 weeks. Pulmonary artery sealing with the Enseal device is feasible and safe in thoracic surgery settings.